2021
DOI: 10.1111/rda.14044
|View full text |Cite
|
Sign up to set email alerts
|

Different expression of LHR, PRLR, GH and IGF1 during testicular development of yak

Abstract: Luteinizing hormone receptor (LHR), prolactin receptor (PRLR), growth hormone (GH) and insulin‐like growth factor 1 (IGF1) have been shown to be key regulators of germ cell development. However, the role of LHR, PRLR, GH and IGF1 in the development of yak testis remains unclear. In this study, we aimed to describe and compare gene expression and protein localization of LHR, PRLR, GH and IGF1 in the development of yak testes. Testes were collected from 6, 24, 36 and 72 months yak, and the kidney, liver, testicu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…Therefore, testicular development and spermatogenesis are key processes affecting the reproductive efficiency in male yaks. Moreover, several functional genes have been reported to regulate testicular development and spermatogenesis in yaks [ 17 19 ]. Recently, miRNAs have been implicated in gene regulation by repressing the translation or degradation of target mRNAs [ 20 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, testicular development and spermatogenesis are key processes affecting the reproductive efficiency in male yaks. Moreover, several functional genes have been reported to regulate testicular development and spermatogenesis in yaks [ 17 19 ]. Recently, miRNAs have been implicated in gene regulation by repressing the translation or degradation of target mRNAs [ 20 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, testicular development and spermatogenesis are critical processes that impact the reproductive efficiency of male Holstein bulls. Researchers have identified several functional genes that regulate testicular development and spermatogenesis in cattle breeds and yaks ( La et al, 2022;Liu et al, 2022;Xu et al, 2018). Moreover, recent studies have implicated miRNAs in gene regulation by repressing the translation or degradation of target mRNAs (Fabian et al, 2010).…”
Section: Rt-qpcr Validationmentioning
confidence: 99%
“…PRL is mainly synthesized and secreted by the lactotroph cells of the anterior pituitary gland and acts via its membrane PRL receptor (PRLR) (6). PRLR has been identified in the testes of various species, including rams (7), rats (8), yaks (9), and humans (4). Studies have revealed that the PRLR in ram testes is expressed by Leydig cells and germ cells in seminiferous tubules, and the expression site and pattern of the receptor gene indicates a crucial role for PRL in the regulation of steroidogenesis and spermatogenesis (7).…”
Section: Introductionmentioning
confidence: 99%